Bilateral chalaziosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
We talk about chalaziosis in case of multiple chalazia. Chalazion is a chronic granulomatous inflammation caused by obstruction of the excretory duct of the Meibomian sebaceous gland, located in the tarsal connective tissue and producing the sebum which contributes to the hydrolipidic film moistening the conjunctiva. The obstruction of its excretory duct causes it to rupture and the consequent foreign body granuloma. STAT1 (1) gain-of-function mutations, constitutional factors, dysvitaminosis A, drugs such as proteasome (2) inhibitors, demodicosis have been hypothesized among the pathogenic factors of chalazion. Dermatologists know the link with idiopathic facial aseptic granuloma and rosacea and differentiate it from other infectious, inflammatory and neoplastic disorders. Ophthalmologists face possible eye complications and intervene surgically when the chalazion does not regress, considering the possible scarring outcomes.